非HIV患者のニューモシスチス肺炎診断におけるファンギテックGテストを用いた(1, 3)-β-D グルカンの評価 - 井手口, 周平 (Oxford University Press, 2021)
Nagasaki University (長崎大学) 博士(医学) Pneumocystis jirovecii pneumonia (PCP) is an opportunistic and life-threatening pulmonary infection with an increasing prevalence among individuals who are human immunodeficiency virus (HIV)-negative. Evidence regarding diagnostic testing of PCP in this patient population is insufficient. We evaluated the performance of serum (1, 3)-β-d-glucan (BDG) using the Fungitec G-test MK kit for diagnosing PCP in non-HIV patients. We retrospectively analyzed data from 219 non-HIV adult patients who underwent bronchoscopy and were tested for P. jirovecii DNA by PCR using lavage samples from the lower respiratory tract. Fifty PCP patients and 125 non-PCP patients were included. The most common underlying diseases were malignancies and systemic autoimmune diseases. Using the serum BDG Fungitec G-test MK test to diagnose PCP, the area under the receiver operating characteristic curve (AUC) was 0.924, whereas the modified cut-off value of 36.6 pg/mL had a sensitivity and specificity of 92.0% and 84.8%, respectively. The AUC for patients with systemic autoimmune diseases was 0.873, and the accuracy of serum BDG test declined when using methotrexate (MTX). In conclusion, the serum BDG test was useful for diagnosing PCP in non-HIV patients; however, the results should be carefully interpreted in case of MTX administration. 長崎大学学位論文 学位記番号:博(医歯薬)甲第1325号 学位授与年月日:令和3年3月22日 Author: Shuhei Ideguchi, Kazuko Yamamoto, Tatsuro Hirayama, Takahiro Takazono, Yoshifumi Imamura, Taiga Miyazaki, Noriho Sakamoto, Koichi Izumikawa, Katsunori Yanagihara, Shimpei Morimoto, Hiroshi Mukae Medical Mycology, myaa101; 2020 Nagasaki University (長崎大学), 博士(医学) (2021-03-22) doctoral thesis